HABIB HUSEIN JA'FAR ISLAMIC EDUCATION STRATEGY MANAGEMENT IN YOUTUBE VIDEOS DA'WAH PERSPECTIVE - Ginting, Mickail; Ritonga, Hasnun Jauhari (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the management of Habib Husein Ja'far's da'wah strategy in YouTube videos about Islamic messages. This research is a qualitative research with qualitative data types. The data collection technique is in the form of observation and library research (library research) obtained from various data related to the things studied, in the form of literature related to this research. The results of the study show that the management of the da'wah strategy used by Habib Husein Ja'far is in the form of lecture breaks, writing pauses and chatting pauses. Habib Husein is more often active in the digital world, covering social media, be it Twitter, Instagram and Youtube. Habib Husein Ja'far's YouTube channel, which has been managed independently from the start, contains studies on da'wah materials on Islam that are light and packaged in an attractive way. The method of conveying Habib Husein Ja'far Al-Hadar's preaching on YouTube has an appeal with the technique of applying a relaxed style of delivery, the Dominant style delivery method, and the animated expressive style delivery method